Effects of Microelements on Drought Resistance of Cotton Plant - Askar Ergashovich, Kholliyev; Umida Toshtemirovna, Norboyeva; Khamida Rakhimovna, Adizova; Flora Abdullayevna, Fayziyeva (International Journal of Psychosocial Rehabilitation, 2020)
The following article deals with the physiological indicators of the effects of microelements on the drought resistance of cotton. Experiments that describe droughtresistant properties - the viscosity and elasticity of the protoplasm, the cellular juice thickness and osmotic pressure, the amount of water that binds in the leaf tissue, the water retention properties of the leaves, and the development of microelementsare depend on the changes of cotton development degrees.